PENGGUNAAN BAHASA INDONESIA PADA SISWA SEKOLAH DASAR INTERNASIONAL SEBAGAI PERSAMAAN IDENTITAS DIRI DI KELAS BAHASA INDONESIA - Fathia Anggriani Pradina (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2021)
Elementary school level students who study at international schools use a foreign language in this context which is English. However, in Indonesian class, they must use Indonesian properly and correctly. The situation of the students in using Indonesian during the Indonesian language course shows their efforts to have the same identity with their teachers who are indeed Indonesian citizens (WNI). They often change the use of English to Indonesian or also insert Indonesian in their English sentences. This phenomenon gives the view that language functions not only as a means of communication but can also be used so that speakers have the same identity.